Early Aptian marine incursions in the interior of northeastern Brazil following the Gondwana breakup - Fauth, Gerson; Kern, Henrique Parisi; Villegas-Martín, Jorge; De Lira Mota, Marcelo Augusto; dos Santos Filho, Marcos Antonio Batista; Santa Catharina, Amanda [UNESP]; Leandro, Lilian Maia; Luft-Souza, Fernanda; Strohschoen, Oscar; Nauter-Alves, Andressa; Tungo, Edna de Jesus Francisco; Bruno, Mauro Daniel Rodrigues; et al. (Springer Nature, 2023)
This study reports a set of primeval marine incursions identified in two drill cores, 1PS-06-CE, and 1PS-10-CE, which recovered the Barbalha Formation, Araripe Basin, Brazil. Based on a multi-proxy approach involving stratigraphy, microbiofacies, ichnofossils, and microfossils, three short-lived marine incursions were identified, designated Araripe Marine Incursions (AMI) 1–3. AMI-1 and AMI-2, which occur within the shales of the Batateira Beds (lower part of the Barbalha Formation), were identified by the occurrence of benthonic foraminifera, calcareous nannofossils, dinocysts, and a mass mortality event of non-marine ostracods. AMI-3 was recognized in the upper part of the Barbalha Formation, based on the occurrence of ichnofossils and planktonic foraminifera. The observation of the planktonic foraminifera genus Leupoldina for the first time in the basin indicates early Aptian/early late Aptian age for these deposits, and the first opportunity of correlation with global foraminifera biozonation. Our findings have implications for the breakup of the Gondwana Supercontinent, as these incursions represent the earliest marine-derived flooding events in the inland basins of northeastern Brazil.